A potential material for tissue engineering: Silkworm silk/PLA biocomposite - Cheung, Hoi-Yan; Lau, Kin-Tak; Tao, Xiao-Ming; Hui, David (Composites. Part B, Engineering, 2008)
Poly(lactic acid) (PLA), a kind of well recognized biodegradable polymer, was reinforced by silkworm silk fibers to form a completely biodegradable and biocompatible biocomposite for tissue engineering applications. The influence on the mechanical and thermal properties of the biocomposite in relation to the length and weight content of silk fibers is studied in this paper. Through the micro-hardness test, optimized fiber length and weight content of silk fibers used to make a better strength silk fiber/PLA biocomposite was determined. Tensile property test and thermal analyses including differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and thermogravimetry analysis (TGA) for the silk fiber/PLA biocomposite with specified fiber length and weight content were then conducted to investigate its property changes in comparison to a pristine PLA sample. Experimentally, it was found that the fiber length and weight content of silk fibers are key parameters that would substantially influence the hardness of the biocomposite samples. For microscopic observations, good wettability of the fibers inside the biocomposite was seen. The surface of the fibers was well bonded with the matrix, as observed by a SEM image of fractured sample. As a result, it was found that the use of silk fibers can be a good candidate, as reinforcements for the development of polymeric scaffolds for tissue engineering applications.